The contribution of social theories to information system research. (1st January 2013) - Beldi, Adel; Azan, Wilfrid
The concept of the IT user is an object of fascination in information systems research. This paper attempts to explore the theoretical issues regarding this actor, considered as changeable and erratic by social theories such as the human agency theory and the structuration theory. Our approach, which does not claim to be exhaustive, focuses primarily on a review of a list of information system papers that have used social theories. Our paper attempts first to provide an overview of the evolution regarding the place of users in IS research, second, to identify the contributions made by some IS papers that have harnessed social theories, and third, to explore potential research topics using social theories.